2004
DOI: 10.1104/pp.104.045542
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arabidopsis Lysine-Rich Arabinogalactan-Protein AtAGP17 Mutant (rat1) That Results in a Decreased Efficiency of Agrobacterium Transformation  

Abstract: Arabinogalactan-proteins (AGPs) are a family of complex proteoglycans widely distributed in plants. The Arabidopsis rat1 mutant, previously characterized as resistant to Agrobacterium tumefaciens root transformation, is due to a mutation in the gene for the Lys-rich AGP, AtAGP17. We show that the phenotype of rat1 correlates with down-regulation of AGP17 in the root as a result of a T-DNA insertion into the promoter of AGP17. Complementation of rat1 plants by a floral dip method with either the wild-type AGP17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 66 publications
5
125
1
4
Order By: Relevance
“…Another potential explanation is that SA signaling also contributes in planta to resistance to Agrobacterium infection, but through an NPR1-independent pathway (10). It has been reported that Agrobacterium rapidly reduces the host systemic acquired resistance by downregulating PR gene expression and decreasing the free SA level by 40% within 1 h after infection (34). It is conceivable that this effect is mediated through NPR1; an inactivating mutation in NPR1 would abrogate the pathogen's ability to disable the plant defenses, resulting in enhanced host resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential explanation is that SA signaling also contributes in planta to resistance to Agrobacterium infection, but through an NPR1-independent pathway (10). It has been reported that Agrobacterium rapidly reduces the host systemic acquired resistance by downregulating PR gene expression and decreasing the free SA level by 40% within 1 h after infection (34). It is conceivable that this effect is mediated through NPR1; an inactivating mutation in NPR1 would abrogate the pathogen's ability to disable the plant defenses, resulting in enhanced host resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher SA concentrations, inhibiting bacterial cell growth could be another strategy in the plant's defensive arsenal. Agrobacterium in turn appears to have evolved a mechanism to stymie the host defenses (34) and may even capitalize on the inhibitory effects of SA on vir gene expression to conserve Col-0 (WT) 33% (n ϭ 69) 33% (n ϭ 51) 24% (n ϭ 37) 3% (n ϭ 37) NahG 47% (n ϭ 30) 48% (n ϭ 54) 38% (n ϭ 29) 5% (n ϭ 38) npr1-1 17% (n ϭ 35) 2% (n ϭ 42) 9% (n ϭ 23) 0% (n ϭ 23) cpr5-2 22% (n ϭ 36) 18% (n ϭ 76) 3% (n ϭ 40) 0% (n ϭ 33) Col-0 (WT) 34% (n ϭ 61) 19% (n ϭ 63) LOX2 9% (n ϭ 171) 9% (n ϭ 155)…”
Section: Discussionmentioning
confidence: 99%
“…AGPs were confirmed to be involved in A. tumefaciens transformation (Nam et al, 1999). Interestingly, AGP17 (rat1 mutant) appears to be involved in host defense reactions and signaling (Gaspar et al, 2004;Gelvin, 2010a). Other two rat mutans, ratT8 and ratT9, were identified to be mutated in the genes coding for receptor-like protein kinases (Zhu et al, 2003).…”
Section: Plant Factors Involved In the Attachment Of A Tumefaciens Tmentioning
confidence: 95%
“…Lysine-Rich Arabinogalactan-Protein AtAGP17 [22] and an Arabidopsis glucomannan 4-betamannosyltransferase 9 gene AtCslA-09 [21] are both involved in the bacterial attachment to the plant cell wall. After attaching to the plant cell, the next important step of the infection is the transfer of the T-DNA into the host cell.…”
Section: Arabidopsismentioning
confidence: 99%
“…These studies identified approximately 40 plant genes (proteins) which are involved in Agrobacteriummediated transformation including, for example, the Arabinogalactan-Protein AtAGP17, the Reticulon domain proteins (BTI1-3), the VirE2 interacting proteins (Vip1 and Vip2), importins, histones and several other factors involved in the ubiquitin-proteasome complex [reviewed in 10,11]. Inactivation of such genes by insertion mutagenesis or gene silencing resulted in an attenuated tumor phenotype or even resistance to Agrobacterium transformation [7,8,[14][15][16][21][22][23], while their overexpression in transgenic plants increased their Agrobacterium sensitivity [15,24,25]. Although certain contributing genes, e. g. VIP1 and CSLA9, seem to be expressed constitutively [16,21], Agrobacteriuminfection induced the expression of a complete set of host genes involved in the transformation process [20].…”
Section: Introductionmentioning
confidence: 99%